P84 Co-Polyimide-based Tubular Carbon Membrane: Effect of Pyrolysis Temperature - Norazlianie, Sazali; W. N. W., Salleh; N., Arsat; Z., Harun; K., Kadirgama (Universiti Teknologi Malaysia, 2019)
In this study, the effect of carbonization temperature on the performance of carbon membrane was being investigated. P84 co-polyimide-based tubular carbon membrane were fabricated through the dip-coating technique. The prepared membranes were characterized by using the thermogravimetric analysis and scanning electron microscopy. CO2, N2, and CH4 pure gas were utilized in determination of the carbon membrane’s permeation attributes. In order to enhance the membrane’s performance, carbonization process was performed in Ar environment; with the flow rate of 200 ml/min. The carbonization process was done at various temperature, namely 600 oC, 700 oC, 800 oC and 900 oC in a constant heating rate of 3 oC/min. The increased in the temperature of carbonization leads to the production of small pores size carbon membrane. Carbon membrane prepared at 800 oC showed the highest CO2/CH4 and CO2/N2 selectivity of 63.2±5.2 and 61.3±1.7, respectively.